Urban form influence on microclimate and building cooling demand - Daniela Maiullari (A+BE: Architecture and the Built Environment)
As a determinant of urban microclimate and building energy performance, urban form plays a critical role when planning city transitions toward decarbonization. Even though energy use for cooling has tripled between 1990 and 2016 globally, and global increase in temperature is reinforcing this trend, the complex relationship between urban form and cooling demand remains understudied. Additionally, in urban climate conditions where the Urban Heat Island (UHI) further contributes to a temperature increase, a comprehensive quantification of form-dependent microclimate impacts on building cooling demand is limited by the methodological approaches employed.